Willingness to pay for certified wood materials among builders joinery and carpentry manufacturers in Malaysia - Mohamed, Shukri; Abdullah, 'Ainol Mardhiah (Forestry Department Peninsular Malaysia, 2014)
This study examines uptake and willingness to pay for certified wood materials among builders' joinery and carpentry manufacturers in Malaysia. A self-administered questionnaire was used to collect data from 240 manufacturers. The response rate was 24.6% with 46 fully-completed questionnaires used in the final analysis. Only 46% of the respondent firms are currently using certified wood materials. Their decision to use such wood materials is to improve their image and reputation in the wood products market, and to meet customer demand for certified timber products. The average amount of premium paid by these manufacturers is about 4.5%. Only 17 of these 25 manufacturers (68%) who are not currently using certified wood materials would do so in the future. These firms' interest in using the wood material is associated with the expected potential of increasing their sales and profit, as well as to improve their image and reputation in the market. However, only 9 of these manufacturers (56%) would be willing to pay a premium for the wood raw materials. The amount of premium these manufacturers would be willing to pay for the certified wood materials is approximately 3.2%. There is potential for an increase use of certified wood materials and willingness to pay a price premium by builders' joinery and carpentry manufacturers in Malaysia.